An Overview of Status and Development Trend of Aquaculture and Fisheries in Nepal - Alok Dhakal; Meena Pandey; Preeti Kayastha; Gresha Suwal; Binita Suwal (Advances in Agriculture)
Although Nepal is a landlocked country, it has abundant water resources that enhance its potential for fisheries and aquaculture activities. But, only a few percentages of the total water resources have been utilized properly. Despite a satisfactory growth in pond fish production over the last 15 years with 73,693 Mt. of fish produced in the fiscal year 2020/21, there has not been much significant advancement in the fisheries sector as expected. Some of the major challenges encountered by farmers are lack of technical knowledge, lack of capital, scarcity of good quality fingerlings, quality feed, diseases, and lack of good market infrastructure. We recommend government authorities to address the problems as aquaculture and fisheries are important sectors that contribute to nutrition for rural people and employment opportunities for many individuals.